Evaluation of The Online Learning System at MBA (Case Study: School of Business and Management Bandung Institute of Technology) (The Indonesian Journal of Business Administration, 2021)
Through developing business, management and entrepreneurship, ITB founded the School of Business and Management of ITB on 30 September 1990. SBM ITB is located in Bandung, Jatinangor and Jakarta. Due to the pandemic, every school activity, including SBM ITB, postponed their face-to-face activity until an unknown time. Despite the number of postgraduate students being raised, the quality output of studies has decreased due to online classes and makes students feel less effective with the online studies, MBA ITB students also felt unmotivated with online learning due to having to manage the school between the home’s atmosphere. The methodology for this research is using a questionnaire process based on DELES’s quality of learning and Bersin’s employee experience transitioned into student experience will be conducted from MBA ITB students. From both quantitative and qualitative processes. The form of the questions is a likert scale, using 5 response points and using regression analysis to find the relationship between student experience and quality of learning.After performing a test using simple linear regression, the independent variables (Student Experience) towards the quality of learning were all found to be significant predictors of student experience from employee experience’s Bersin from Deloitte. Based on the result, the study concluded that the quality of learning survey result is in a good shape, meanwhile some of the student experiences’ dimensions need to be improved. Therefore, this study proposes a solution is conducted in order to improve the quality of learning and student experience in MBA ITB. Keywords: Quality of Learning, Student Experience, Online learning